Porcine Health Management - Maes, Dominiek; Segalés, Joaquim
Porcine Health Management (PHM) is an open access peer-reviewed journal that aims to publish relevant, novel and revised information regarding all aspects of swine health medicine and production. The journal provides a venue for global research on swine health and production, including infectious and non-infectious diseases, reproduction, epidemiology, management, economics, genetics, housing, nutrition, animal welfare and ethics, legislation, food safety, drugs and surgery. PHM also welcomes submissions on relevant clinical cases related with all areas mentioned above. In addition, the journal covers wildlife aspects considered to have an interrelation with domestic swine.